Hemodynamic and behavioral changes in older adults during cognitively demanding dual tasks (2021)
Introduction: Executive functions play a fundamental role in walking by integrating information from cognitive-motor pathways. Subtle changes in brain and behavior may help identify older adults who are more susceptible to executive function deficits with advancing age due to prefrontal cortex deterioration. This study aims to examine how older adults mitigate executive demands while walking during cognitively demanding tasks. Methods: Twenty healthy older adults (M = 71.8 years, SD = 6.4) performed simple reaction time (SRT), go/no-go (GNG), n-back (NBK), and double number sequence (DNS) cognitive tasks of increasing difficulty while walking (i.e., dual task). Functional near infra-red spectroscopy (fNIRS) was used to measure the hemodynamic response (i.e., oxy- [HbO2] and deoxyhemoglobin [HbR]) changes in the prefrontal cortex (PFC) during dual and single tasks (i.e., walking alone). In addition, performance was measured using gait speed (m/s), response time (s), and accuracy (% correct). Results: Using repeated measures ANOVAs, neural findings demonstrated a main effect of task such that ∆HbO2 (p =.047) and ∆HbR (p =.040) decreased between single and dual tasks. An interaction between task and cognitive difficulty (p =.014) revealed that gait speed decreased in the DNS between single and dual tasks. A main effect of task in response time indicated that the SRT response time was faster than all other difficulty levels (p <.001). Accuracy performance declined between single and dual tasks (p =.028) and across difficulty levels (p <.001) but was not significantly different between the NBK and DNS. Conclusion: Findings suggest that a healthy older adult sample might mitigate executive demands using an automatic locomotor control strategy such that shifting conscious attention away from walking during the dual tasks resulted in decreased ∆HbO2 and ∆HbR. However, decreased prefrontal activation was inefficient at maintaining response time and accuracy performance and may be differently affected by increasing cognitive demands. © 2021 The Authors. Brain and Behavior published by Wiley Periodicals LLC